2020
DOI: 10.36692/cpaqv-v12n3-1
|View full text |Cite
|
Sign up to set email alerts
|

Percepção Da Qualidade De Vida De Professores Das Redes Públicas E Privadas Frente À Pandemia Do Covid-19

Abstract: The COVID-19 virus had its origin in the city of Whuan - China. This virus has a clinical picture ranging from asymptomatic infections to severe respiratory conditions. Through this virus it was decreed by the World Health Organization as being a pandemic, with it routine aspects were compromised, causing new solutions to be proposed. Quality of life was one of the factors affected by this virus, especially when we relate to teachers, as they had to adapt to new teaching methods, moving from classroom to virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 2 publications
0
3
0
13
Order By: Relevance
“…No Brasil, foi identificado aumento da frequência de pessoas que se sentiram frequentemente isoladas, tristes ou deprimidas, ansiosas ou nervosas, bem como de relatos de dificuldades relativas ao sono (Almeida et al, 2020). Essa é uma realidade condizente com achados de pesquisas internacionais (Huang e Zhao, 2020;Guo et al, 2020;Lei et al, 2020;Rossi et al, 2020;Gallagher, 2020) e nacionais (Alvarenga et al, 2020;Almeida et al, 2020;Barros et al, 2020;Gomes et al, 2021;Malta et al, 2020;Pavani et al, 2021;Rocha et al, 2021;Silva et al, 2021;Souza et al, 2021) que avaliaram a saúde mental da população durante a atual pandemia.…”
Section: Redução Da Renda Familiar Dos Docentes Da Educação Básica: Discussões Sobre Os Resultadosunclassified
“…No Brasil, foi identificado aumento da frequência de pessoas que se sentiram frequentemente isoladas, tristes ou deprimidas, ansiosas ou nervosas, bem como de relatos de dificuldades relativas ao sono (Almeida et al, 2020). Essa é uma realidade condizente com achados de pesquisas internacionais (Huang e Zhao, 2020;Guo et al, 2020;Lei et al, 2020;Rossi et al, 2020;Gallagher, 2020) e nacionais (Alvarenga et al, 2020;Almeida et al, 2020;Barros et al, 2020;Gomes et al, 2021;Malta et al, 2020;Pavani et al, 2021;Rocha et al, 2021;Silva et al, 2021;Souza et al, 2021) que avaliaram a saúde mental da população durante a atual pandemia.…”
Section: Redução Da Renda Familiar Dos Docentes Da Educação Básica: Discussões Sobre Os Resultadosunclassified
“…Above all, the instruments used in the two studies to assess quality of life and stress were different. Alvarenga et al (2020), in turn, used the brief WHOQOL as well as Pedrolo et al (2021), however, they found a low level of perception of the QoL of public and private teachers, where only the physical domain was at a satisfactory level. In the mental domain, the negative evaluation was unanimous in all the studies mentioned, corroborating the results found here.…”
Section: Discussionmentioning
confidence: 99%
“…O domínio relativo à Saúde Mental avalia a capacidade psicológica do indivíduo no enfrentamento dos desafios inerentes à condição humana, como capacidade de lidar com fatores estressantes, por exemplo, instabilidade no emprego, doenças graves, traumas, dentre outros (Alvarenga et al, 2020). Nesse contexto, as mulheres foram mais acometidas, com risco aumentado de ter baixa qualidade de vida nas dimensões Saúde Mental e Vitalidade, e baixos índices em Capacidade Funcional e Estado Geral de Saúde, com pouca diferença entre os gêneros nesses dois últimos.…”
Section: Discussionunclassified